Persistence of Temephos 1% Sand Granule Against Aedes aegypti L. Larvae in Amphoe Hankha, Chainat Province - เจตนะจิตร, เกรียงศักดิ์; เลาห์ประเสริฐ, ประชุมพร; แผ่พร, พรรณเกษม (Disease Control Journal, 2009)
This research objective was to examine the persistence of Temephos 1% sand granulea against Aedes aegypti (L.) laboratory strain and Chainat - field strain larvae. Both tap and rain water were used in 200-liter containers. Usability of water was divided into 2 groups: regularly used (Temephos concentration was not stable) and never used (Temephos concentration was stable). Persistent time was examined from 1 to 16 weeks. The results showed that in laboratory strain: Temephos 1 % activated 100 percent-larvae killed in regularly used tap and rain water were 5 and 1 weeks respectively. Temephos 1 % activated 100 percent-larvae killed in never used tap and rain water were 8 and 7 weeks respectively. In Chainat – field strain: Temephos 1 % activated 100 percent-larvae killed in regularly used tap water was 4 weeks. Temephos 1 % activated 100 percent-larvae killed in never used tap and rain water were 2 and 1 weeks respectively.